ANALISIS SENTIMEN MENJADI DASAR PERBAIKAN KUALITAS PELAYANAN HOTEL DI TRIPADVISOR - Ringo, Tiurma Ristiani Siringo; Novita, Novita (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2024)
Tripadvisor is a website that contains information on travel and tourist destinations and applications that users can access to provide reviews based on places that Tripadvisor users have visited. This study aims to determine the performance of the algorithm used in predicting and providing improvements in the quality of hotel services on Tripadvisor based on negative sentiment. This research data collection was carried out using documentation techniques. This type of research is qualitative research with sentiment analysis techniques. The results of the study show that the performance of the algorithm used is good with an accuracy value of 87%. In the negative sentiment analysis results, service quality improvements are made by providing recommendations to hotels on TripAdvisor, among others, the hotel staff must be more careful when fulfilling customer requests, maintaining the cleanliness of hotel rooms, improving the quality of food ingredients by choosing more competent chefs, and providing training to food servers so that they can be more polite to customers. Keywords: Sentiment Analysis; Service Quality; Logistic Regression